Intracellular and extracellular rhomboid shaped crystalline inclusions in a case of IgG lambda restricted plasma cell myeloma: a case report and review of the literature - Rizack Tina; Matoso Andres; Treaba Diana O (BMC, 2010)
Abstract The presence of crystalline inclusions in plasma cell myeloma is a rare phenomenon and cases have been reported with rod, needle, and rectangular shaped crystals. Here, we present a case of IgG lambda restricted plasma cell myeloma with rhomboid shaped intracellular crystalline inclusions and extracellular crystal depositions in the bone marrow. Since rhomboid crystal depositions can be seen in other clinical conditions such as pseudogout, this case invites consideration of plasma cell myeloma in the differential diagnosis of patients with rhomboid crystalline deposition in the bone marrow and in sites/organs other than the bone marrow.